Metoder för parasitundersökning i fårbesättningar - Hammarsten, Elin (2018)
Infection with endoparasites is a problem in sheep flocks worldwide. In order to avoid treating animals with anthelmintics unnecessarily, or missing animal groups in need of treatment, it is important that there are diagnostic tools that effectively detects sheep groups with a high degree of infection. A common way of estimating the degree of infection in sheep farms is to analyze the number of parasitic eggs in samples from a certain number of animals in the flock. The result is then used to estimate the overall degree of infection in the flock. The purpose of this study was first to investigate the distribution of parasitic eggs between the individuals in a relatively small flock of sheep as well as to investigate what endoparasite species were present in the flock. The third, and most important purpose of the study, was to investigate to what extent the number of individual fecal samples included in a composite sample influences the accuracy of the estimation of the flock mean.